User centered design for medical visualization - Dong, Feng; Ghinea, Gheorghita; Chen, Sherry Y. (IGI Global, 2008)
"This book features a comprehensive review of advances in medical visualization and human-computer interaction. It investigates the human roles during a visualization process, specifically motivation-based design, user-based design, and perception-and-cognitive-based design. It also provides real-world examples and insight into the analytical and architectural aspects of user centered design"--Provided by publisher